Development of a model compatible with solar assisted cylindrical energy storage tank and variation of stored energy with time for different phase change materials - Esen, M; Ayhan, T (Pergamon-Elsevier Science Ltd, 1996)
In this work, the performance of a solar assisted cylindrical energy storage tank is investigated theoretically. A model describing the transient behavior of a phase change energy storage unit is used. The model of the tank holds the numerical description of a short term (by day) heat-storage tank. Tn the tank, the energy is stored as the latent heat of the phase change material (PCM). In the tank, the PCM is packed in cylinders, and the heat transfer fluid (HTF) flows parallel to it. The basis of the model is the enthalpy method. The resulting set of equations is solved by means of the Gauss-Seidel iteration process. Selected computer simulations are drawn versus some parameters of the model, and the heat storage capacities of different PCMs, which can be used as heat storage materials for domestic heating by heat pumps, were determined and compared. Results show that the PCM, cylinder radius, the mass how rate, and the inlet temperature of the HTF must be chosen carefully in order to optimize the performance of the tank. Copyright (C) 1996 Elsevier Science Ltd
Keywords: solar energy storage; phase-change materials; latent heat; simulation; enthalpy method; heat pump